Rediscovering Teaching in University: A Scoping Review of Teacher Effectiveness in Higher Education - Mastrokoukou, Sofia; Kaliris, Andronikos; Donche, Vincent; Chauliac, Margot; Karagiannopoulou, Evangelia; Christodoulides, Pavlos; Longobardi, Claudio (Frontiers in Education, 2022)
Teacher effectiveness plays a prominent role in the learning process. Existing scientific evidence in higher education (HE) is quite limited, as most studies on teacher effectiveness focus on elementary and secondary education. Although effective teaching is important, the definition of what constitutes effective teaching and the methods used to assess teacher effectiveness have changed over time. Little is known about how different tools are used to conceptualise and assess teacher effectiveness at HE. The goal of this review is threefold: first, to map the literature on the construct mentioned above; second, to illustrate the instruments that have been used to assess teacher effectiveness at HE. Third, our review aims to highlight the most effective teaching approaches according to the literature. In the selection process, emphasis was placed on studies that measured instructional processes in terms of student outcomes. Particular attention was paid to studies that assess teacher effectiveness in terms of added value to student achievement and student satisfaction. International research was reviewed with particular attention to Southeastern Europe, as student achievement and teacher effectiveness are indicated as topics of great interest to the Greek state. Twenty-six studies were included. The results show that there is no universally accepted definition of effective higher education teaching. Effective teaching may manifest itself in high scores on measures of student achievement or in rewarding classroom interactions. Based on this principle, the way teacher effectiveness is defined is closely intertwined with proposed solutions in educational policy. In examining the most effective teaching styles, it has been shown that student-centred teaching styles are perceived by students as more effective, more engaging, and are associated with positive gains in student achievement. However, several studies have not concluded why different teachers use different teaching styles in similar contexts. Although this review represents a step forward in our understanding of teacher effectiveness in HE, further research is needed to evaluate it from different perspectives and in different contexts. In particular, there is a great need to assess effectiveness from the students' perspective and to assess effective classroom climate.